A evasão no ensino superior: ProUni e FIES como políticas de acesso e redução da evasão: o que demonstram as pesquisas? - Leite, Aurenice dos Santos (2021)
Dropping out is a social problem which affects all levels of students. This search presents a reduction in higher education highlighting factors that cause students to abandon university in the context of the implemented ProUni and FIES policies that amplify the access and maintenance of students in course. It is a bibliographic research, with exploratory-descriptive features, from mapping on databases that provide thesis, dissertations, and articles which discuss the theme. The critical understanding of the selected material was based on authors that discuss the theme. Our goals are: i) to address the concept of dropping out; ii) to analyze the results of Higher Education Census for the last ten years; iii) to present the scholarship programs - PROUNI and the higher education funding - FIES; and iv) to map researches which address ProUni and FIES as access and maintenance policies in higher education. The systematic search in the main academic production indexes showed that the number of investigations and the production of thesis and articles concerning higher education dropping out have increased mainly in the past five years. The analysis of the selected material leads to conclude that the term “dropping out” is used in different meanings, including as student mobility, which is a positive aspect. In terms of educational policies in higher education, the analyzed researches highlight their neoliberal features when considering the privatization model with less financing for public education and in favor of the education entrepreneurs. From such a model, access to private education, as ProUni and FIES, end up being needed by the lower classes. Although such policies do not ensure all the students’ maintenance in courses, since there are several reasons involved, it requires policies in different areas. Dropping out has an important relationship with social inequality. Therefore, this work concludes that dropout rates in higher education are still significant and have increased as an important theme for research.